2019
DOI: 10.18510/hssr.2019.7260
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Stability in Dual Banking System: Comparison Between Conventional and Islamic Banks in Malaysia

Abstract: Purpose of Study: This paper aims to explore whether Islamic banks are more stable when compared with conventional banks in a dual banking system. Methodology: This research employs Pooled OLS methodology for 42 banks, including 27 conventional banks and 15 Islamic banks, for the period of 2005-2016. Results: The study suggests that Islamic banks are less stable compared to conventional banks in overall banking sector. Furthermore, it is found that big Islamic banks are less stable than big convent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…The Islamic dummy appears to be negative and significant, indicating that Islamic banks are less stable than their conventional counterparts. One of the possible arguments for this finding might be that conventional banks are bigger than Islamic banks, which makes them more stable (Alaeddin, Khattak, and Abojeib, 2019). These findings are in line with Wahid and Dar (2016), who compare the stability of Islamic and conventional banks in Malaysia and found that Islamic banks are lesser stable.…”
Section: B Impact Of Competition and Diversification On Stability (Isupporting
confidence: 72%
See 1 more Smart Citation
“…The Islamic dummy appears to be negative and significant, indicating that Islamic banks are less stable than their conventional counterparts. One of the possible arguments for this finding might be that conventional banks are bigger than Islamic banks, which makes them more stable (Alaeddin, Khattak, and Abojeib, 2019). These findings are in line with Wahid and Dar (2016), who compare the stability of Islamic and conventional banks in Malaysia and found that Islamic banks are lesser stable.…”
Section: B Impact Of Competition and Diversification On Stability (Isupporting
confidence: 72%
“…Loan ratio is used to control the credit exposure of banks, as they might have significant effects on the banks. Furthermore, it is argued that banks that have higher loan ratios are likely to have poor performance and are risky and unstable stable (Alaeddin, Khattak, and Abojeib, 2019). Ideally, a higher loan ratio should increase the level of riskiness; however, it will not be surprising if this research finds a positive relationship between loan ratio and stability measure.…”
Section: Independent Variablesmentioning
confidence: 71%
“…This proxy has been used exhaustively in the literature (Čihák and Hesse; Demirgüç-Kunt and Detragiache, 2011). Z-score is measured at bank-level and is considered as a powerful predictor of banks' default (Alaeddin et al , 2019; Cihak and Hesse, 2010). It employs the accounting data to calculate the solvency risk of a bank.…”
Section: Methodsmentioning
confidence: 99%